Demand-aware price policy synthesis and verification services for Smart Grids - Mancini, Toni; Mari, Federico; Melatti, Igor; Salvo, Ivano; Tronci, Enrico; Gruber, Jorn Klaas; Hayes, Barry; Prodanovic, Milan; Elmegaard, Lars (2014 IEEE International Conference on Smart Grid Communications (SmartGridComm), 2014)
In management tasks for modern electricity networks the stakeholders face typically two conflicting objectives: maximization of income (increasing demand) and reduction of demand peaks (reducing costs). To improve management of electricity distribution networks, an integrated service-based methodology is presented in this paper. Namely, the proposed approach: i) computes the operational constraints in order to improve utilization of the whole network; ii) enforces those constraints by focusing on each network substation separately; iii) verifies that probability of violating those constraints in nonnominal cases is fairly low. The feasibility of the approach has been tested tested by using a realistic scenario taken from an existing medium voltage Danish distribution network. In such scenario, the proposed method improves the network utilization and offers economic benefits for all the principal participants, i.e. DSOs, retailers and end users.